Prostitusi Online Sebagai Kejahatan Kemanusiaan terhadap Anak: Telaah Hukum Islam dan Hukum Positif - Oksidelfa Yanto (Universitas Islam Negeri Jakarta, 2016)
Online Prostitution as Humanity Crimes against Children: in the Perspective of Islamic Law and Positive Law. Disclosure of online prostitution case is a clear proof that social media is becoming a powerful tool for prostitution promotion. Prostitution is a result of the unlimited use of online social media. Therefore, as a country with Muslim population as majority, the state must take steps against any form of prostitution. If prostitution is not eradicated, it will be fast-growing business. Also, it will make Indonesia considered as a country that maintains immoral behaviors.DOI: 10.15408/ajis.v16i2.4449